Thickness-Dependent NIR LSPR of Curved Ag/TiS2 Bilayer Film - Yongjun Zhang; Fan Zhang; Yaxin Wang (Molecules, 2020)
We demonstrated that the localized surface plasmon resonance (LSPR) features of Ag/TiS2 nanostructures were dependent on the sublayer thickness. The Ag/TiS2 bilayer film was obtained by the self-assembly method and magnetron sputtering. The thickness was controlled by changing the sputtering time when the sputtering powers were the same. When the Ag thickness decreased from 50 nm to 5 nm, the LSPR was tuned from the visible region to the Near Infrared (NIR) region. When the TiS2 thickness decreased from 60 nm to 2 nm, the LSPR shifted from the IR to NIR region. Analysis showed the thickness changes of Ag and TiS2 resulted in the changed carrier density, which led to the thickness-dependent shift of the LSPR.